Anatomical characterization of athetotic and spastic cerebral palsy using an atlas‐based analysis. Issue 2 (4th June 2013) - Yoshida, Shoko; Faria, Andreia V.; Oishi, Kenichi; Kanda, Toyoko; Yamori, Yuriko; Yoshida, Naoko; Hirota, Haruyo; Iwami, Mika; Okano, Sozo; Hsu, John; Li, Xin; Jiang, Hangyi; et al.
<x xml:space="preserve">Abstract</x> Purpose To analyze diffusion tensor imaging (DTI) in two types of cerebral palsy (CP): the athetotic‐type and the spastic‐type, using an atlas‐based anatomical analysis of the entire brain, and to investigate whether these images have unique anatomical characteristics that can support functional diagnoses. Materials and Methods We retrospectively analyzed the DTI of seven children with athetotic‐type, 11 children with spastic‐type, and 20 healthy control children, all age‐matched. The severity of motor dysfunction was evaluated with the Gross Motor Function Classification System (GMFCS). The images were normalized using a linear transformation, followed by large deformation diffeomorphic metric mapping. For 205 parcellated brain areas, the volume, fractional anisotropy, and mean diffusivity were measured. Principal component analysis (PCA) was performed for the Z‐scores of these parameters. Results The GMFCS scores in athetotic‐type were significantly higher than those in spastic‐type (P < 0.001). PCA extracted anatomical components that comprised the two types of CP, as well as the severity of motor dysfunction. In the athetotic group, the abnormalities were more severe than in the spastic group. In the spastic group, significant changes were concentrated in the lateral ventricle and periventricular structures. Conclusion Our results quantitatively delineated anatomical characteristics that reflected the functional findings in two types of CP. J. Magn. Reson. Imaging 2013;38:288–298. © 2013 Wiley Periodicals, Inc.